2017
DOI: 10.1111/jnc.14221
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity‐dependent local activation of dendritic unfolded protein response promotes expression of brain‐derived neurotrophic factor in cell soma

Abstract: Unfolded protein response (UPR) has roles not only in resolving the accumulation of unfolded proteins owing to endoplasmic reticulum (ER) stress, but also in regulation of cellular physiological functions. ER stress transducers providing the branches of UPR signaling are known to localize in distal dendritic ER of neurons. These reports suggest that local activation of UPR branches may produce integrated outputs for distant communication, and allow regulation of local events in highly polarized neurons. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 87 publications
(86 reference statements)
1
19
0
Order By: Relevance
“…In addition to controlling BDNF expression, XBP1 also initiates a positive feedback loop in which BDNF increases XBP1 mRNA splicing through the activation of IRE1 . A recent report identified the signaling event engaging IRE1 downstream of the BDNF receptor as phosphorylation by protein kinase A, also validating the role of XBP1s in the autoamplifying loop of BDNF to drive its own expression . Another study confirmed the effects of XBP1 on neuronal plasticity and applied these findings to a model of AD.…”
Section: Xbp1s As a Core Mediator Of Synaptic Plasticitymentioning
confidence: 80%
“…In addition to controlling BDNF expression, XBP1 also initiates a positive feedback loop in which BDNF increases XBP1 mRNA splicing through the activation of IRE1 . A recent report identified the signaling event engaging IRE1 downstream of the BDNF receptor as phosphorylation by protein kinase A, also validating the role of XBP1s in the autoamplifying loop of BDNF to drive its own expression . Another study confirmed the effects of XBP1 on neuronal plasticity and applied these findings to a model of AD.…”
Section: Xbp1s As a Core Mediator Of Synaptic Plasticitymentioning
confidence: 80%
“…5e and Table S4), similar to the findings obtained in Tg XBP1s animals. We also detected important changes in proteins related to extracellular matrix, suggesting an impact to secretory pathway proteostasis (Table S4) Importantly, accumulating evidence suggest that UPR mediators, and more specifically XBP1, have alternative functions in the nervous system by controlling synaptic plasticity 24 and dendritogenesis 25,26 . Importantly, the appearance of senescent cells in brain function was (Table S2, Table S3 and Table S4).…”
Section: Main Textmentioning
confidence: 77%
“…XBP1s also upregulates brain-derived neurotrophic factor (BDNF) that is a major factor involved in synaptic plasticity in health and disease. Activation of Protein kinase A (PKA) via cyclic AMP by different agents in the brain can in turn influence IRE1α (Saito et al, 2018 ). Inhibition of IRE1α ameliorated the social behavior deficits, a commonly observed trait in some neuropsychiatric disorders (Crider et al, 2018 ).…”
Section: The Unfolded Protein Responsementioning
confidence: 99%
“…Amongst the genes, BDNF was identified as a key transcriptional target of XBP1s (Martínez et al, 2016 ). Neuronal activity induced by glutamate increases IRE1α/XBP1 signaling in dendrites with an enhanced BDNF transcription, whilst the addition of recombinant BDNF treatment upregulated IRE1α/XBP1 (Saito et al, 2018 ). Protein Kinase A (PKA) was shown to be an important mediator in this process.…”
Section: Ire1α Signalingmentioning
confidence: 99%